فعالية تطبيق طريقة “Qatar Debate” لتعمق مهارة الكلام في المناظرة العربية لفصل “متقدم” بدورة ناطق عربية باري كديري - Batul, Zahadatul; Rizki, Restu Budiansyah (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2025)
The design of this study is focused on measuring the effectiveness of the application of the "Qatar Debate" method for mastery of speech skills in Arabic debates in the Mutaqodddim class at the Naatiq Arabiyyah Pare Kediri Course. The formulation of the questions in this study is: (1) How is the application of the "Qatar Debate" method for mastery of speaking skills in Arabic debate in the Mutaqoddim class in the Naatiq Arabiyyah Pare Kediri Course? (2) How effective is the application of the "Qatar Debate" method for the mastery of speaking skills in Arabic debate in the Mutaqoddim class in the Naatiq Arabiyyah Pare Kediri Course? This study uses a quantitative research method. The data collection used in this study was tests, documentation, interviews, and observations. The researcher explained the results of this study, namely: (1) The application of the "Qatar Debate" method for mastering speaking skills has an important role in improving the quality of learning, especially in learning speaking skills. This method is applied as a form of developing Arabic debate learning. (2) The average score obtained by students (89.00) is higher than the hypothetical score (80.00). So this method is effective in helping students to develop fluency in speaking, fluency and intonation as well as the richness of language styles in speaking Arabic orally.